Normal-high IGF-1 level improves pregnancy rate after ovarian stimulation in women treated with growth hormone replacement therapy. Issue 12 (2nd November 2022) - Ly, Nathalie; Dubreuil, Sophie; Touraine, Philippe
Abstract : Objective: Growth hormone (GH) and insulin-like growth factors (IGFs) are not mandatory for reproductive life, but data suggest their synergistic action with follicle-stimulating hormone throughout ovarian folliculogenesis. We aimed to evaluate the association of IGF-1 level on clinical pregnancy rate after ovarian stimulation, with or without intrauterine insemination, in women with GH deficiency (GHD) treated with GH replacement therapy (GHRT) at conception. Design and methods: Data from 19 women with both GHD and hypogonadotropic hypogonadism referred to our reproductive medicine department were retrospectively collected. IGF-1 levels were assessed in a single laboratory, and values were expressed in s.d. from the mean. Results: Amongst the seven patients receiving GHRT during ovarian stimulation, higher IGF-1 levels were significantly associated with clinical pregnancy (+0.4 s.d. vs–1.6 s.d., P = 0.03). Amongst the 24 pregnancies obtained by the 19 infertile patients, pregnancy loss was less frequent with the addition of GHRT than without (1 miscarriage out of 8 total pregnancies vs 4 miscarriages out of 16 total pregnancies). Conclusions: This is the first study evaluating the association of IGF-1 level on clinical pregnancy rate in GH-treated women at conception. When taking care of female infertility due to hypogonadotropic hypogonadism, practitioners should enquire about the associated GHD and IGF-1 levels. To ensure higher clinical pregnancy chances, practitioners should aim for IGF-1 values at conception, ranging from 0 s.d. to +2 s.d., and, if necessary, could discuss initiation or increase GH treatment. Prospective studies should help strengthen our results.